On the drag coefficient of flat and non‐flat solid particles of irregular shapes: An experimental validation study. Issue 10 (20th July 2022) - Roostaee, Amin; Faghani, Ali; Vaezi, Mahdi
Abstract: The very wide varieties of geometries of irregular particles makes it difficult to study their motion also propose a simple and general equation to estimate their drag coefficient ( C D ). The goal of this research is to (1) experimentally validate the general C D correlation previously proposed by the authors of this article as a simple tool to estimate the C D of spherical to highly irregular particles over a wide ranges of Re from 0.001 to 300, 000, and (2) examine and expand the reference model particles proposed by the authors to represent a wide range of irregular shapes (60 non‐flat and 36 flat). A comparison between the C D experimentally measured using reference model particles over a range of Re from 9 to 2481 and the C D estimated using general C D correlation, also comparing with C D correlations by others, demonstrated the accuracy and simplicity of the proposed general C D correlation.